Effect of support type and crystal form of support in the catalytic gasification of old corrugated containers using Fe-based catalysts. (September 2022) - Lu, Wang; Lei, Shuaishuai; Chen, Xu; Sun, Lin; Xia, Sunwen; Bartocci, Pietro; Chen, Yingquan; Yang, Haiping; Chen, Hanping
Highlights: The effect of support in Fe-based catalyst on OCCs gasification was studied. Fe/amorphous Al2 O3 shows best H2 selectivity (51.46%) due to good Fe dispersity. Fe/TiO2 shows best H2 yield (25.10 mmol/g) due to Fe2 TiO5 solid-melt component. Fe/amorphous Al2 O3 shows good activity and stability on H2 production. Abstract: Catalytic gasification of old corrugated containers with Fe-based catalysts is a promising way to produce renewable H2 along with the utilization of solid waste. In this study, the effect of support type and crystal form of support in Fe-based catalysts on the catalytic gasification of old corrugated containers was systematically investigated. The results show that, the introduction of Fe/γ-Al2 O3, Fe/TiO2, Fe/SiO2, and Fe/ZSM5-30 promote H2 production. Among them, Fe/TiO2 has the highest catalytic activity on H2 yield (25.10 mmol/g) related to the formation of Fe2 TiO5 solid-melt material. Fe/γ-Al2 O3 shows the best H2 selectivity (46.34 %) and good H2 yield (24.19 mmol/g) due to good dispersity of Fe. Further, the order of catalytic effect on H2 selectivity is Fe/amorphous Al2 O3 (51.46 %) > Fe/α-Al2 O3 (46.98 %) > Fe/γ-Al2 O3 (46.34 %). With the increase in cycle index, Fe/amorphous Al2 O3 shows the best catalytic effect on H2 yield (25.56 mmol/g) after 11 indexes due to the formation of Al2 FeO4 . Fe/γ-Al2 O3 shows the best stability on H2 selectivity (∼43 %) after 11 indexes.